Comparative assessment of ethanol and isobutanol addition in gasoline on engine performance and exhaust emissions. (20th July 2018) - Yusoff, M.N.A.M.; Zulkifli, N.W.M.; Masjuki, H.H.; Harith, M.H.; Syahir, A.Z.; Khuong, L.S.; Zaharin, M.S.M.; Alabdulkarem, Abdullah
Abstract: The depletion of fossil fuels is causing great concern and it is important to search for alternatives. Ethanol and isobutanol are suitable for spark ignition engine due to their favorable physicochemical properties that can be blended with pure gasoline to reduce the dependency on petroleum fuels. Six types of fuel blends consisting of ethanol and isobutanol were mixed with gasoline at different volume rates and were tested on a four-cylinder spark ignition engine by varying the engine speeds and engine torques to evaluate their engine performance and exhaust emissions characteristics. The results indicate that the binary blend of E20 gives an increase in torque, brake power and brake thermal efficiency, while the ternary blend of E10iB10 gives an increase in brake specific fuel consumption, compared to that of pure gasoline. In terms of exhaust emissions, E20 and E10iB10 blend show the lowest carbon monoxide and hydrocarbon emissions, respectively, for both conditions. However, all the fuel blends show higher carbon dioxide emissions as compared to pure gasoline. There are no significant differences in nitrogen oxides emissions for all fuel blends with respect to pure gasoline. However, the fuel blends show higher nitrogen oxides emissions at higher engine speeds and torques. Highlights: Blends containing ethanol and/or isobutanol at different volume rates were tested on a four-cylinder SI engine. Binary blend of E20 gives the best results in T, BP, BTE and CO emissions. Ternary blend of E10iB10 gives the best results in BSFC and HC emissions. CO2 emissions are higher for all tested blends. No significant differences of EGT and NOX emissions for all tested blends with respect to PG.